Preserving fragile ecosystems from oil spills – An environmental sensitivity assessment of the east coast of Trinidad. (1st November 2022) - O'Brien-Delpesh, Charmaine; Sinanan, Nyoka; Martin, Hector; Chadee, Aaron
Abstract: Ecosystems remain vulnerable, reducing their resilience without informed planning and management to update oil spill vulnerabilities. An oil spill from an offshore platform was simulated to predict probable oil landing zones off the east coast of Trinidad. Climate, land use, and sedimentation were used to classify the east coast of Trinidad and to identify the geomorphic features that are most susceptible to oil spills. In ArcGIS, physical and biological resources were used to modify NOAA's estuarine classification and build an environmental sensitivity index (ESI) map representing wet and dry seasonal changes. Leatherback sea turtle nesting sites are highly vulnerable; thus, the shoreline classification reflects this. This research identified six intertidal ecosystem indices along the east coast of Trinidad, namely ESI-1, ESI-3, ESI-4, ESI-6 and ESI-10. Mangroves were considered the most sensitive habitat, whereas high wave energy locations were ranked the lowest. This study provides first responders and environmental officials with a methodological approach to determine the locations and areas most vulnerable and develop appropriate response and cleanup strategies/plans before the oil reaches land. Highlights: Biological systems are more impacted by the adverse impact of oil along the coastline. A modified ESI which include biological context is provided. Oil spill modelled with seasonal variation to predict impact on biodiversity is developed. Decision context is provided to inform authorities on how to safely address oil spills in environmentally sensitive areas.